Hyperornithinemia‐hyperammonemia‐homocitrullinuria syndrome in pregnancy: Considerations for management and review of the literature. Issue 1 (14th March 2019) - Ho, Bernice; MacKenzie, Jennifer; Walia, Jagdeep; Geraghty, Michael; Smith, Graeme; Nedvidek, Julie; Guerin, Andrea
Abstract: Hyperornithinemia‐hyperammonemia‐homocitrullinuria (HHH) syndrome is a rare metabolic autosomal recessive urea cycle disorder. Only about 100 patients have been reported in the literature. As the population survives into reproductive years, pregnancy management becomes a new challenge for this clinicians. To our knowledge, there are less than three patients with successful pregnancies and deliveries found in the literature with no specific consensus on management or recommendations for HHH syndrome. We reviewed the current literature regarding pregnancy outcomes, combine it with our experience managing a patient through two successful pregnancies and identify a new concern of fetal intrauterine growth restriction. From this, recommendations for pregnancy management are made, including a detailed protocol for clinicians to use for disease management at delivery and in the post‐partum period.